Mitigation of Subsequent Ovariectomy Responses through Prior Exercise Training in Rats - da Palma, Renata Kelly; Angelis, Kátia De; Shimojo, Guilherme Lemos; Dutra, Marina Rascio Henriques; dos Santos, Camila Paixão; Bernardes, Nathalia; Bolsoni-Lopes, Andressa; Curi, Rui; Gomes, João Lucas; Oliveira, Edilamar Menezes; Irigoyen, Maria Claudia; Malfitano, Christiane (International Journal of Sports Medicine, 2024)
It is well known that cardiometabolic dysfunction gradually increases after menopause, and the sedentary lifestyle can aggravate this condition. Therefore, we compared the effects of aerobic exercise training during the premenopausal period and after ovariectomy (OVX) on metabolic, hemodynamic, and autonomic parameters in an experimental rat model of menopause. The female rats were divided into four groups: control (C), sedentary OVX (SO), trained OVX (TO), and previously trained OVX (PTO). The PTO group was trained for 4 weeks prior to+8 weeks after OVX, and the TO group trained only after OVX on a motor treadmill. Autonomic modulation was evaluated, white adipose tissue (WAT) was removed and weighed, and lipolysis was assessed. The citrate synthase activity in the soleus muscle was analyzed. The trained groups prevented the impairment of baroreceptor reflex sensitivity in relation to SO; however, only PTO reduced the low-frequency band of the pulse interval compared to SO. PTO reduced the weight of WAT compared to the other groups; lipolysis in PTO was similar to that in C. PTO preserved muscle metabolic injury in all types of fibers analyzed. In conclusion, this study suggests that exercise training should be recommended in a premenopausal model to prevent cardiometabolic and autonomic menopause-induced deleterious effects.
Keywords: exercise training; menopause; cardiometabolic state; autonomic dysfunctions